Eurynodes cristatus (Théry, 1934) removed from synonymy with E. coelestis (Kerremans, 1897) (Coleoptera: Buprestidae: Aphanisticini) - Kwast, Tom (Zootaxa, 2025)
Eurynodes cristatus (Théry, 1934) stat. rest. is resurrected to species rank and removed from synonymy with E. coelestis (Kerremans, 1897). A lectotype for E. cristatus is designated and illustrated. Comments on the type specimens and original data labels are provided. Additionally, a diagnosis between females of E. coelestis and E. cristatus is presented.